2012
DOI: 10.1080/19475705.2011.611952
|View full text |Cite
|
Sign up to set email alerts
|

Ambient noise levels in Gujarat State (India) seismic network

Abstract: The Gujarat state seismic network (GSNet), comprising of 50 broadband seismograph (BBS) stations and 40 strong motion accelerographs (SMAs), has been operated and maintained by the Institute of Seismological Research (ISR) since 2006. Nineteen permanent BBS stations are connected through VSAT and the rest are kept in an offline mode. The local geology beneath seismic stations varies from Mesozoic to Quaternary formations. The seismic background noise (SBN) at these stations was calculated and found that it var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…At higher frequencies body waves make a significant contribution to seismic noise (e.g., Roux et al 2005;Koper et al 2010;Landes et al 2010;Wang et al 2010). Various researchers have also observed short period noise well recorded on vertical component, and long period noise prominent on horizontal components of the seismic records (Webb 2002;Kumar et al 2012;Jana et al 2017). De Angelis (2008, however, argued that the horizontal components are noisier than the vertical components due to its sensitivity to the tilts of the seismometers, as the gravity effect is coupled to the horizontal components only.…”
Section: Power Spectral Densitymentioning
confidence: 98%
“…At higher frequencies body waves make a significant contribution to seismic noise (e.g., Roux et al 2005;Koper et al 2010;Landes et al 2010;Wang et al 2010). Various researchers have also observed short period noise well recorded on vertical component, and long period noise prominent on horizontal components of the seismic records (Webb 2002;Kumar et al 2012;Jana et al 2017). De Angelis (2008, however, argued that the horizontal components are noisier than the vertical components due to its sensitivity to the tilts of the seismometers, as the gravity effect is coupled to the horizontal components only.…”
Section: Power Spectral Densitymentioning
confidence: 98%
“…The Deccan trap sites show lesser noise levels, while sites on Jurassic, Cretaceous, and Tertiary formations show moderate noise levels. An earlier study by Kumar et al (2012) using data from 14 broadband seismic stations revealed that stations on soft soils are noisier. A careful comparison between the previous seismic noise level analysis based on data from limited stations and the present analysis with larger amount of data recorded by more seismograph stations for longer duration, provides detailed information about the background noise level of the Gujarat seismic network.…”
Section: Datamentioning
confidence: 99%
“…2b and 3a). Previously, large seismic background noise values in the 2-5 Hz frequency range for stations located on the Quaternary and Tertiary formations were reported 20 , and explained in terms of a combined effect of predominant frequencies and cultural activities. Here, the predominant frequency corresponds to the frequency at which the maximum value of site amplification is observed for a station/site.…”
Section: Seismic Noise Characterizationmentioning
confidence: 94%